Nonequilibrium fractionation of rare earth elements during typhoon-induced event sedimentation - Yanbin Fan; Yunhai Li; Yunpeng Lin; Haidong Li; Hengbo Wang; Haibo Fan; Hannv Zhang; Guicai Zhong; Feng Jiang (Frontiers in Marine Science, 2026)
High-energy, short-lived typhoon deposition can disrupt particle–water interactions, raising the question of whether rare earth elements (REEs) in event deposits still reflect equilibrium-controlled partitioning or instead capture transient, non-equilibrium geochemical states. We sampled a ~0.5–1 cm surface storm layer and underlying background sediments at 11 stations in the northeastern Beibu Gulf on 29–30 September 2024 (20–21 days after Typhoon Yagi), and quantified major/trace elements and REEs by ICP-OES and ICP-MS, integrating grain size/TOC and statistical correlations. Storm deposits show systematically lower ∑REE and LREE concentrations and slightly lower LREE/HREE ratios than background sediments, accompanied by weaker negative Eu anomalies and a shift toward slightly negative Ce anomalies relative to the mild positive Ce anomaly in background deposits. Despite finer textures and elevated TOC in the storm deposits, the canonical grain-size/adsorption control collapses, with ∑REE exhibiting little to no correlation with grain-size under storm conditions. Critically, storm deposits display pronounced LREE–HREE decoupling: LREE behave quasi-conservatively with “event-scale inertia”, whereas HREE respond more sensitively to non-equilibrium carrier reorganization and rapid settling. This selective decoupling provides a diagnostic geochemical fingerprint for identifying event-driven sedimentation and highlights the need to incorporate kinetic/time-scale effects when interpreting REE-based proxies in dynamic environments.